A new hope. - Ng, Wai San. (2010)
A New Hope is a video documentary produced by a group of graduating students from the Wee Kim Wee School of Communication and Information (WKWSCI) at the Nanyang Technological University (NTU), Singapore as part of their Final Year Project (FYP).